Influence of Physico-Chemical Factors of Gharana Wetland Soil on the prevalence of Keratinophilic Fungal Inhabitants. - SHIFALI SHARMA,; GEETA SUMBALI, (International Journal of Pharma and Bio Sciences, 2018)
Investigations were conducted to assess the ecological factors regulating the prevalence of keratinophilic fungi in the soil of Gharana wetland, R.S. Pura (Jammu), an important stop over site for numerous migratory birds. Soil samples collected from 8 different sites were found to be rich in organic matter due to the presence of keratinous substrates in the form of feathers, claws, etc. The soils were nearly neutral to slightly alkaline with moderate electrical conductivity favouring the growth and dispersal of keratinophilic fungi. Further, these soil samples showed high content of macronutrients viz., nitrogen, phosphorous, potassium and sulphur as well as presence of micronutrients like iron, copper, manganese and zinc. All these physico-chemical factors of the wetland soil played an important role in the prevalence of both dermatophytic and non- dermatophytic keratinophilic species.